Effects of the tailored intervention program in lowering blood glucose levels and diabetes distress among patients with diabetes in Indonesia: a randomized controlled trial - Satriya Pranata; Shu-Fang Vivienne Wu; Tsae-Jyy Tiffany Wang; Shu-Yuan Liang; Difran Nobel Bistara; Yeu-Hui Chuang; Kuo-Cheng Lu; Aric Vranada (Jurnal Ners, 2023)
Introduction: Blood glucose levels and diabetes distress are the foremost factors contributing to diabetes treatment outcomes and managements. No tailored intervention program was implemented for patients with diabetes in Indonesia. This study aimed to investigate the effectiveness of a tailored intervention program in lowering blood glucose levels and diabetes distress among patients with diabetes patients in Indonesia.